The Effect of Jelajah Alam Sekitar (JAS) Approach toward the Natural Science Learning Outcomes for Students with Intellectual Disability - Fauzi, Muhammad Rizqianto; ., Sudarsini; Hastuti, Wiwik Dwi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
Students with intellectual disability require specialized learning that can improve a natural science outcomes by using Neighborhood Nature Exploration approce. The purpose of this study is to determine the effect of natural surrounding exploration approach towards Learning outcomes of natural sciences for students with intellectual disability. The research design is Pre experimental of one group pretest-posttest design. Subjects of this study were 8 students with intellectual disability in the grade II. The collection of data was by providing pretest, treatment and post-test. The data analysis used was ladder - Wilcoxon signed. Hypothesis test results showed that the value Tcount Â (36) > Ttable (6), then Ho is rejected. The conclusion was that there are significant effect of natural surrounding exploration approach towards Learning outcomes of natural sciences for students with intellectual disability.Siswa tunagrahita memerlukan pembelajaran khusus yang dapat meningkatkan hasil belajar IPA dengan menggunakan pendekatan Jelajah Alam Sekitar. Tujuan kajian ini adalah untuk mengetahui pengaruh pendekatan Jelajah Alam Sekitar terhadap hasil belajar IPA bagi siswa tunagrahita. Kajian ini menggunakan rancangan penelitian Pre experimental design dengan bentuk One Group Pretest-Posttest Design. Subjek kajian ini adalah 8 siswa tungrahita kelas II. Pengumpulan data dengan memberikan pretest, treatment dan post test. Analisis data menggunakan uji jenjang â bertanda Wilcoxon. Hasil uji hipotesis menunjukkan bahwa nilai Thitung Â (36) > Ttabel (6), maka Ho ditolak. Kesimpulannya adalah terdapat pengaruh pendekatan Jelajah Alam Sekitar terhadap hasil belajar IPA pada siswa tunagrahita.